THE EFFECT OF WORKLOAD, BURNOUT, AND WORK MOTIVATION ON NURSE PERFORMANCE - Kurniawati, Fivi; Fikaris, Muhammad Fiarry; Eryani, Ika Septiana; Rohendi, A.; Wahyudi, Bayu (Jurnal Aplikasi Manajemen, 2023)
Nurse Performance plays a crucial role in ensuring the quality of service delivery within hospitals. However, nurses often face significant stress due to heavy workloads and the demanding nature of patient care, leading to burnout. In order to support optimal performance, it is imperative for nurses to possess strong work motivation. This study aimed to investigate the impact of workload, burnout, and work motivation on nurse performance within a specified public hospital in Batam. An observational analytic approach with non-probability sampling was employed, and the study included 111 participants. Data analysis and processing were conducted using a statistical software program. The findings revealed that workload and burnout exerted a negative influence on nurse performance, while work motivation had a positive effect. Workload, burnout, and work motivation collectively and partially impacted nurse performance. Consequently, it is vital for hospital management to prioritize factors that affect nurse performance. Through effective management and the mitigation of stressors in the hospital work environment, the overall well-being of healthcare workers can be improved, resulting in elevated levels of health. Notably, this study utilized the latest literature references and research instruments to ensure robust findings.